Will the housing wealth effect compensate the macro-economy? Evidence from Taiwan’s domestic consumption - Cheng, Hong-Jhong; Wang, Nan-Yu; Peng, Chien-Wen; Huang, Chih-Jen (International Journal of Strategic Property Management, 2020)
This paper examines the relationship between the escalation in housing prices and categories of Taiwan’s domestic consumption. While disposable income remains constant, a rapid escalation in housing prices should have a negative impact on unaffordability within society. However, under the hypothesis of the housing wealth effect, an increase in housing values should compensate the macro-economy by increasing consumption in the GDP calculation. Taiwanese data from 2007Q1 to 2018Q1 were adopted as the sample. From the vector error correction model results, it was found that over the course of the long-run equilibrium relationship, there was a statistically significant positive relationship that the society consumes more on durable goods of communication-related nature, as well as on non-durable goods such as personal clothing and accessories and leisure/cultural tourism. As for the short-run dynamic adjustment, there was a statistically significant positive relationship that the society consumes more in the durable goods component categories. It was identified that transportationrelated consumption accounted for the major part of the durable goods component. Therefore, with the rapid escalation in housing prices, it was observed that these consumption would compensate the consumption figures in the GDP calculation in Taiwan, thereby providing evidence that housing prices were related to macroeconomic performance.